Implementasi Strategi Pembelajaran Berdiferensiasi pada Pembelajaran Sejarah di SMA Negeri 16 Kota Bandung - Maulidan, Aldi Cahya; Saripudin, Didin; Supriatna, Nana (Universitas Hamzanwadi, 2025)
So far, history learning has given little space to students because it emphasizes memorization, but in differentiated learning, students are given space to develop their interests and talents. This happens because creativity is formed when students are given space to think and create according to their interests and talents. This study aims to explain the implementation of differentiated learning strategies in history subjects in high schools. This study uses a qualitative approach with a case study research type, using participant observation data collection techniques, structured interviews, and documentation studies. The data analysis used is data reduction, data presentation, and conclusion. The researcher found that the implementation of differentiated learning is effective in improving the quality of the teaching and learning process. Differentiated learning, carried out by adjusting content, processes, and evaluations according to the needs, interests, and abilities of students, can create a learning environment that is more inclusive and responsive to individual differences. The success of differentiated learning can be seen from the responses of students, who stated that students feel enthusiastic and motivated because they can create a product that is the result of their abilities and creativity. Support from the school in providing facilities and training for teachers also contributes to the success of the implementation of differentiated learning. Thus, differentiated learning has been proven to be able to increase the effectiveness of history learning and encourage optimal academic development of students. Then, differentiated learning can be used as inspiration in implementing learning based on the principles of the independent curriculum.